2019
DOI: 10.1159/000503143
|View full text |Cite
|
Sign up to set email alerts
|

Changes in CD4<sup>+</sup>CD25<sup>+</sup>FoxP3<sup>+</sup> Regulatory T Cells and Serum Cytokines in Sublingual and Subcutaneous Immunotherapy in Allergic Rhinitis with or without Asthma

Abstract: <b><i>Background:</i></b> Few studies have directly compared the immunologic responses to specific subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT). <b><i>Objective:</i></b> We aimed to directly compare clinical efficacy and immunological responses between SLIT and SCIT in allergic rhinitis (AR) sensitized to house dust mites. <b><i>Methods:</i></b> Sixty-seven patients (age 5–55 years) with moderate-severe <i>De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…270,285 Furthermore, in dust mite-allergic subjects both SCIT and SLIT treatment induced higher presence of CD4+CD25+FoxP3+ Tregs compared to both controls groups and base line levels. 288 However, there was a correlation with clinical improvement only for SLIT.…”
mentioning
confidence: 94%
“…270,285 Furthermore, in dust mite-allergic subjects both SCIT and SLIT treatment induced higher presence of CD4+CD25+FoxP3+ Tregs compared to both controls groups and base line levels. 288 However, there was a correlation with clinical improvement only for SLIT.…”
mentioning
confidence: 94%
“…SLIT and SCIT upregulated CD4 + CD25 + FoxP3+ Tregs. However, only SLIT showed clinical improvement related to Tregs ( Xian et al, 2020 ). Despite these results, SCIT is just recommended as an adjunct to pharmacotherapy in individuals with asthma, and SLIT is not recommended ( Cloutier et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 6 The CD4 + CD25 + Foxp3 + Treg cells induced by tolerogenic dendritic cells (DCs) in the oral mucosa mediate immune tolerance, thus improving the clinical efficacy after SLIT. 7 SLIT has no risk of severe systemic reactions, which is considered an advantage over SCIT, because allergens are mostly captured by tolerogenic DCs before they reach the mast cells during SLIT. 6 It has been suggested that SCIT contributes to the phenotypic deviation of Th2 cell responses to a protective Th1 profile, which enables SCIT to manifest earlier IFN-γ secretion than SLIT.…”
mentioning
confidence: 99%
“… 6 It has been suggested that SCIT contributes to the phenotypic deviation of Th2 cell responses to a protective Th1 profile, which enables SCIT to manifest earlier IFN-γ secretion than SLIT. 7 A recent study indicated that Dermatophagoides pteronyssinus (Der p)-specific IgG4 levels in asthma treated with SCIT were almost 30 times higher than those in asthma treated with SLIT. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation